Odpowiedzi

2010-02-21T15:31:19+01:00
A) 4x+4 -x =-5
3x+=-5-4
3x=-9/:3
x=-3
4* (-3) + 4 - (-3) = -5
-12 + 4 +3=-5
-5=-5

b)-3x - 3 - x =9
-4x=9+3
-4x=12 /:4
x=-3
9 - 3 +3=9
9=9

2010-02-21T15:32:11+01:00
A) 4x+4-x=-5
3x=-9/:3
x=-3
b)-3x-3-x=9
-4x=12/:-4
x=-3
c)3x+6+2x=4
5x=-2/:5
x=-0,4
d)x-7-6x-10=3
-5x=20/:-5
x=-4
e)-3x=-1/:-3
x=0,3
Najlepsza Odpowiedź!
2010-02-21T16:25:02+01:00
A).4x+4-x=-5
3x+4=-5
3x=-5-4
3x=-9:3
x=-3
Sprawdzenie:
3*(-3)+4=-5
-9+4=-5
-5=-5
b).-3(x+1)-x=9
-3x-3-x=9
-4x-3=9
-4x=12/:(-4)
x=-3
Sprawdzenie:
-3*(-3)-3-(-3)=9
9-3+3=9
9=9
c).3(x+2)+2x=4
3x+6+2x=4
5x+6=4
5x=4-6
5x=-2/:5
x=-0,4
Sprawdzenie:
3*(-0,4)+6+2*(-0,4)=4
-1,2+6-0,8=4
4,8-0,8=4
4=4
d).x-7-2(3x+5)=3
x-7-6x-10=3
-5x-17=3
-5x=3+17
-5x=20/:(-5)
x=-4
Sprawdzenie:
-4-7-6*(-4)-10=3
-11+24-10=3
13-10=3
3=3
e).2x-8-5x=-9
-3x-8=-9
-3x=-9+8
-3x=-1/:(-3)
x=1:3(jedna trzecia)
Sprawdzenie:
-3*1:3(jedna trzecia)-8=-9
-1-8=-9
-9=-9
f).2(8-x)-3(9-x)=0
16+2x-27-3x=0
-1x-11=0
-1x=11/:(-1)
x=-11
Sprawdzenie:
16+22-27+33=0
49-49=0
0=0
g).-(3x-1)+5x-2=1
-3x+1+5x-2=1
2x-1=1
2x=2/:2
x=1
Sprawdzenie:
-(3*1+1)+5*1-2=1
-3+1+5-2=1
-2+3=1
1=1
h).3(x-2)-5x=10
3x-6-5x=10
-2x-6=10
-2x=16/:(-2)
x=-8
Sprawdzenie:
3*(-8)-6-5*(-8)=10
-24-6+40=10
10=10
i).(4x-5)-2(x+3)=-4
4x-5-2x-6=-4
-2x-11=-4
-2x=7/:(-2)
x=-3,5
Sprawdzenie:
4*(-3,5)-5-2*(-3,5)-6=-4
14-5-7-6=-4
9-7-6=-4
-4=-4